Geological storage of carbon dioxide (CO₂) : geoscience, technologies, environmental aspects and legal frameworks (Woodhead Publishing Limited, 2013)
Provides an overview of the fundamentals of the geological storage of CO2. Explores the environmental, social and regulatory aspects of CCS including CO2 leakage from geological storage facilities, risk assessment of CO2 storage complexes and public engagement in projects, and the legal framework for CCS. Also, focuses on a variety of different projects and includes case studies.
Keywords: Geological carbon sequestration.; elektronické knihy; electronic books